Etnobotânica histórica e biodiversidade amazônica: plantas úteis descritas na obra “O país das amazonas” (1885) do Barão de Santa-anna Nery - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2023)
Historical ethnobotany seeks to understand, through historical records, the use of plants in order to contribute to the development of science, using documents and historical works as a tool, such as the book “O País das Amazonas” from 1885. The objective of this work was to analyze the work “The country of the Amazons” by the Brazilian propagandist Barão de Santa-Anna Nery in order to inventory, recover and organize ethnobotanical information on the use of useful and medicinal plants described in the book. The plant species described in the work were inventoried and, depending on the availability of information, the scientific names were updated in the Plants of the World, Reflora and Tropicos databases. The medicinal species had their traditional therapeutic indications compared with the pharmacological studies present in PubMed, Science Direct and Google Scholar databases. Of the 154 species listed in the manuscript, 131 were included in the study, with 45 botanical families mentioned in which Fabaceae (23) and Arecaceae (16) were the most representative, 36 medicinal plants were listed, but only 24 species had medicinal uses defined by the barão, of these, the use of 19 species were corroborated with pharmacological studies. The main indications of medicinal plants reported were: astringent (5), purgative (5), febrifuge (4) and vermifuge (4). Regarding non-medicinal species, 95 species were categorized, in which food use (31) and construction in general (19) stood out. With regard to the origin of the plants, it was found that 109 species were native, 9 exotic, 7 cultivated and 6 naturalized, thus, the importance of preserving native flora was verified, mainly in places where the community uses traditional knowledge. about plants for therapeutic purposes, avoiding interruption in the transmission of this knowledge. Given the observed, most of the therapeutic indications have already been corroborated with pharmacological studies. It is important to understand the use of plants in the historical context of society so that it contributes to new research and new purposes, highlighting those with therapeutic purposes to achieve the creation of a traditional herbal product. It was also possible to rescue the work of a great Brazilian propagandist, in addition to valuing the history of the Amazon and Brazilian literature.
Keywords: Conhecimento tradicional; Planta medicinal; História natural; Etnofarmacologia